2020
DOI: 10.1080/15384101.2020.1859197
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19), human erythrocytes and the PKC-alpha/-beta inhibitor chelerythrine –possible therapeutic implication

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes COVID-19. Until now, diverse drugs have been used for the treatment of COVID-19. These drugs are associated with severe side effects, e.g. induction of erythrocyte death, named eryptosis. This massively affects the oxygen (O 2 ) supply of the organism. Therefore, three elementary aspects should be considered simultaneously: (1) a potential drug should directly attack the virus, (2) eliminate virus-infected host cells and (3) preserve eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 74 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…In the case of respiratory viral infection, protein kinase C activation facilitates nuclear transport of the viral ribonucleoproteins in the infected cells and their subsequent budding at the cell membrane. Hence, protein kinase C is an ideal choice for drug targeting and chelerythrine as an inhibitor of protein kinase C-α/-β mediated viral genome transport would be of a great importance in the induction of apoptosis in the SARS-CoV-2 infected cells [ 16 ].…”
Section: Chelerythrine Has Protein Kinase C Inhibitory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of respiratory viral infection, protein kinase C activation facilitates nuclear transport of the viral ribonucleoproteins in the infected cells and their subsequent budding at the cell membrane. Hence, protein kinase C is an ideal choice for drug targeting and chelerythrine as an inhibitor of protein kinase C-α/-β mediated viral genome transport would be of a great importance in the induction of apoptosis in the SARS-CoV-2 infected cells [ 16 ].…”
Section: Chelerythrine Has Protein Kinase C Inhibitory Activitymentioning
confidence: 99%
“…Suppression or inhibition of PKC has protective role in erypthosis and prevention of nuclear transport of the viral ribonucleoproteins in infected cells and also dysregulation of the viral replication. [ 11 , 12 , 16 , 48 ] Anti-inflammatory activity Proper inhibition of the body’s inflammatory response in patients with COVID-19 is crucial in the treatment. Chelerythrine has anti-inflammatory activity and can exert this effect by different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that protein kinase C alpha and beta inhibitors have a pro-apoptotic effect in nucleated cells, and this creates a hostile environment for intracellular parasites including viruses. This can enhance the antiviral activity of antivirus drugs [37]. The dual activity (kinase/ protease) of PGs could make them very promising as anti-COVID-19 agents.…”
Section: Resultsmentioning
confidence: 99%
“…Given the aforementioned results, we next hypothesized that inflammatory and lipid alterations experienced by COVID-19 severe patients would be affecting hematological parameters such as erythrocytes and hemoglobin, the most important players in oxygen and carbon dioxide transportation between the lungs and tissues which is strongly compromised in ICU patients. Erythrocytes also display an important role in immune mechanisms against SARS-CoV-2 infection capturing the virus through gangliosides and sialoglycoprotein glycophorin A (GPA) that act as receptors and deliver to macrophages for elimination [47] . Decreased hemoglobin concentration and erythrocyte number were observed in serum samples of G3 patients independently of T2DM or obesity preexistence.…”
Section: Discussionmentioning
confidence: 99%